Does Ethnic Diversity in Schools Affect Occupational Choices? - Damiano Pregaldini; Simone Balestra; Uschi Backes-Gellner (Institute of Labor Economics (IZA), 2022)
We study how two distinct dimensions of peer ethnic diversity (ethnic fractionalization and ethnic polarization) affect occupational choice. Using longitudinal administrative data and leveraging variation in ethnic composition across cohorts within schools, we find evidence for two opposing effects. Ethnic fractionalization increases the likelihood of students sorting into people-oriented occupations while ethnic polarization reduces this likelihood. Using data on social and cognitive skills, we provide evidence that exposure to higher levels of ethnic fractionalization enhances the students' formation of social skills and increases the likelihood of students sorting into people-oriented occupations where the returns to these skills are higher.
Keywords: H75; I21; J18; J24; 330; ethnic diversity; fractionalization; polarization; school; occupational choice